Technical progress and sustainable growth in the manufacturing sector of North American countries, 1984-2022: A stochastic frontier analysis - César Lenin Navarro-Chávez (Economies, 2025)
This article presents an estimation of a stochastic frontier model using a translogarithmic production function to identify the impact of production factors - labor and capital - along with CO2 emissions and technical progress on the value added of the manufacturing sector in North American countries over the 1984-2022 period. The model also provides estimates for technical efficiency, scale efficiency, and technological change, allowing for a comparative analysis of these indicators' evolution within the manufacturing sectors of Canada, Mexico, and the United States. The findings indicate that capital exerts the strongest influence on manufacturing value added, followed by labor. CO2 emissions exhibit the anticipated negative effect on the sector's value added. Notably, the average technical efficiency of Mexico's manufacturing sector is higher than that of Canada and the United States over the studied period. Regarding technological change, the United States demonstrates the highest values, followed by Canada, with both nations displaying an upward trend throughout the years, while Mexico shows a declining trend in this indicator.
Keywords: 330; stochastic frontier analysis; manufacturing sector; North America; CO2 emissions; technical efficiency; technological change